Vertebrobasilar thrombosis: Diagnosis, management, and the use of intra-arterial thrombolytics| - Becker, Kyra J.; Purcell, Laura L.; Hacke, Werner; Hanley, Daniel F. (Critical care medicine, 1996)
Objectives - To review the diagnosis and management of vertebrobasilar thrombosis and to discuss the use of thrombolytics in the treatment of this disease. - Data Sources - Selected references discussing epidemiology, anatomy, pathophysiology, diagnosis, therapy, and rehabilitation of vertebrobasilar occlusive disease. - Study Selection - Studies addressing acute intervention and outcome in the therapy of vertebrobasilar thrombosis were reviewed. - Data Extraction - Only those studies with angiographic documentation of arterial thrombosis and, in the case of thrombolysis, recanalization, were considered valid. - Data Synthesis - Thrombosis of the vertebrobasilar system is a highly fatal disease and should be treated as a neurologic emergency. The key to effective management depends on early recognition of the symptom complex and a thorough understanding of the anatomy and pathophysiology of the disease process. - Conclusions - A timely, integrated, multidisciplinary approach to the patient with vertebrobasilar thrombosis can improve outcome. The use of thrombolytics in the treatment of vertebrobasilar occlusion holds promise but the benefits have not yet been proven in a controlled, randomized study. - (Crit Care Med 1996; 24:1729-1742)